(untitled) (PerCursos, 2007)
A educação intercultural, no contexto das lutas sociais contra os processos crescentes de exclusão social inerentes à globalização econômica, propõe o desenvolvimento de estratégias que promovam a construção de identidades particulares e o reconhecimento das diferenças, ao mesmo tempo em que sustentem a inter-relação crítica e solidária entre diferentes grupos. Partindo da questão; “culturas diferentes podem conversar entre si?”, este artigo apresenta uma conceituação operacional de educação intercultural, elaborada a partir dos estudos desenvolvidos na Europa. Verifica a necessidade de se recolocar a proposta de educação intercultural, considerando a especificidade da formação das identidades culturais e dos processos de integração interétnica no Brasil. E propõe uma perspectiva epistemológica da complexidade, com base nas premissas de Gregory Bateson, para compreender e para orientar o desenvolvimento de contextos educativos que promovam a articulação entre diferentes contextos subjetivos, sociais e culturais. Palavras-chave: educação intercultural. pluralidade cultural. identidade. transversalidade. epistemologia. complexidade.Abstract: The cross-cultural education, in the context of social struggles against the increased process of social exclusion inherent in the economic globalization proposes the development of strategies which provide for the specific identity construction and the recognition of the differences, while it supports the critical and sympathetic interrelationship among the different groups. Departing from the main question “can different cultures communicate with each other?”, this article presents an operative conceptualization of cross-cultural education, elaborated based on the studies carried out in Europe. It concludes with the need of restating the proposal of the cross-cultural education, considering the characteristics of the construction of the cultural identities and of the processes of cross-ethnical integration in Brazil. It also proposes an epistemological approach of the complexity, based on the premises of Gregory Bateson, for the understanding and the orientation of the development of educational contexts, which bring about the articulation of different subjective, social and cultural contexts. Key Words: Cross-cultural education. cultural plurality. identity epistemology. complexity.